High Folic Acid Intake during Pregnancy Lowers Body Weight and Reduces Femoral Area and Strength in Female Rat Offspring - Pedro S. P. Huot; David W. Dodington; Rebecca C. Mollard; Sandra A. Reza-López; Diana Sánchez-Hernández; Clara E. Cho; Justin Kuk; Wendy E. Ward; G. Harvey Anderson (Journal of Osteoporosis)
Rats fed gestational diets high in multivitamin or folate produce offspring of altered phenotypes. We hypothesized that female rat offspring born to dams fed a gestational diet high in folic acid (HFol) have compromised bone health and that feeding the offspring the same HFol diet attenuates these effects. Pregnant rats were fed diets with either recommended folic acid (RFol) or 10-fold higher folic acid (HFol) amounts. Female offspring were weaned to either the RFol or HFol diet for 17 weeks. HFol maternal diet resulted in lower offspring body weights (6%, P=0.03) and, after adjusting for body weight and femoral length, smaller femoral area (2%, P=0.03), compared to control diet. After adjustments, HFol pup diet resulted in lower mineral content (7%, P=0.01) and density (4%, P=0.002) of lumbar vertebra 4 without differences in strength. An interaction between folate content of the dam and pup diets revealed that a mismatch resulted in lower femoral peak load strength (P=0.01) and stiffness (P=0.002). However, the match in folate content failed to prevent lower weight gain. In conclusion, HFol diets fed to rat dams and their offspring affect area and strength of femurs and mineral quantity but not strength of lumbar vertebrae in the offspring.